Metamorphic P–T Evolution and In Situ Biotite Rb–Sr Geochronology of Garnet–Staurolite Schist From the Ramba Gneiss Dome in the Northern Himalaya - Gou, Long-Long; Long, Xiao-Ping; Yan, Hao-Yu; Shu, Tian-Chu; Wang, Jing-Yu; Xu, Xiao-Fei; Zhou, Feng; Tian, Zhi-Bo (Frontiers in Earth Science, 2022)
The North Himalaya gneiss domes provide the window for looking into the deeper crust and record abundant clues of continent collisional orogenesis. This study carried out detailed petrology, in situ LA-ICP-MS biotite Rb-Sr dating, and phase equilibrium modelling on garnet–staurolite–two-mica schist in the Ramba gneiss dome, in order to constrain metamorphic P–T evolution and the timing of metamorphism. A clock-wise P–T path, involving an early prograde process that evolves from ~540 ºC at ~4.4 kbar to ~630 ºC at ~6.0 kbar, was constructed to garnet–staurolite–two-mica schist in the Ramba gneiss dome. In situ LA-ICP-MS biotite Rb-Sr analysis yielded two metamorphic ages of 37.17 ± 5.66 and 5.27 ± 3.10 Ma, corresponding to the timing of retrograde cooling, and the cooling age of the dome following the thermal resetting by the emplacement of ca. 8 Ma leucogranite pluton in the core of the dome, respectively. The peak metamorphism is inferred to be older than ca. 37 Ma. Based on these results and the data previously published, the garnet–staurolite–two-mica schist recorded the Eocene crustal thickening following the Indian-Asia collision, and later exhumation process.